HD44892: the youngest (or oldest?) gas-harbouring debris disc around an intermediate-mass star - Miley, J (Oxford University Press, 2026)
We present the first detections of gas around a 2.1Myr old debris disc-bearing intermediate-mass star, HD44892. Gas is detected both in 12CO (2−1) emission through ALMA (Atacama Large Millimeter/submillimeter Array) Band 6 observations and in absorption in Caii K and H, seen with high-resolution UVES (Ultraviolet and Visual Echelle Spectrograph) spectroscopy. 13CO and C18O (2−1) are not detected. The star exhibits a 12 μm fractional excess of 7.86+0.11-2.27, placing it in the transition stage between protoplanetary and debris discs. Our detection of 1.3mm emission yields the dust mass of 0.019 ± 0.009M⊙ assuming 115K temperature. The 13CO non-detection places an upper limit on CO gas mass of ~10-2 M⊙. The 12CO detection yields a CO gas mass of (7.86 ± 2.05) × 10-5 or (1.62 ± 0.17) × 10-4 M⊙ assuming a gas temperature of 20 or 50K, respectively. These should be considered as lower limits since 12CO emission may be optically thick. With UVES, we find variability in Caii K and H lines, which can be interpreted by transiting circumstellar gas, ruling out interstellar absorption as their origin. Both the dust mass, which is within an order of magnitude of HD141569, and the gas mass derived here indicate a late gas dispersal stage of the protoplanetary disc. Through our analysis, we deem the alternative age of 800Myr unlikely. © The Author(s) 2025. Published by Oxford University Press on behalf of Royal Astronomical Society.